Autism and Gender : From Refrigerator Mothers to Computer Geeks - Jack, Jordynn, 1977- (Book collections on Project MUSE., 2014)
"The CDC estimates that 1 in 110 children in the US have an autism spectrum disorder, and over the last decade the cause of autism has become a highly contested topic in the media as well within medical, scholarly, and autistic communities. Speculation about why and how a growing number of people, especially boys, have been diagnosed with autism spectrum disorders has ranged widely, from parenting practices and vaccines to environmental and genetic factors. Jordynn Jack suggests that as these discourses have proliferated, autism has become a "rhetorical phenomenon" in that it prompts attempts at persuasion through arguments, appeals to emotions, and various representational strategies in vigorous and sometimes vitriolic debates. In this study, Jack takes up the rhetorical dimensions of autism, especially how popular and scientific experts have argued for theories about the etiology of autism spectrum disorders. In particular, Jack focuses on the ways in which assumptions about gender inform popular understandings of the causes and effects of autism. Two well-known gendered theories that have been associated with autism include the "refrigerator mother" theory of the 1950s, which purported that cold, emotionless mothers caused autism, and the Extreme Male Brain theory, which suggests that autism is a disorder of highly systematic thinking associated with male geeks. Theories such as these and others provide opportunities to examine how gendered assumptions fill in gaps in knowledge and authority about autism. More broadly, this analysis offers new insights on how rhetorical inquiry can contribute to larger conversations about gender and disability"--